Bioremediation of Crude Oil-Contaminated Water and Sediments from the Shatt Al-Arab River (SAR) - Wisam Abdul-Ameer Farid1 , Wasen Abdul-Ameer Ali1 , Aseel Nadum Al-Salman2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the SAR, the oil-degrading bacteria (O-DB) are widespread, forming 8 % to 14 % of heterotrophic bacteria(HB). The O-DB numbers and biodegradability of petroleum hydrocarbons (PHY) are important in summer(SU) and sediments (SE) compared to winter (WI) and water (WA). The common O-DB retrieved from theSAR are Pseudomonas sp. (PS), Pseudomonas putida (PP), Pseudomonas fluorescens (PF), Pseudomonasaeruginosa (PA), Pseudomonas cepacia (PC), Corynebactrium sp. (CO), Bacillus sp. (BA), Bacillus cereus(BC), Bacillus subtilis (BS), Flavobacterium sp. (FL), Aeromonas sp. (AE), Arthrobacter sp. (AR), Vibriosp. (VI), Nocardia sp. (NO), Acintobacter sp. (AC), Micrococcus sp. (MI), and Staphylococcus sp (ST). Themost effective O-DB utilized more than 52 % of oil in 21-days. A mixed culture made of mutant PP+ARutilized 93 % of oil during the same period. The oil biodegradation rates in the SAR have been restrictedby biotic and abiotic factors. By providing these factors to the oil-contaminated sites would improve thedegradation rates. The biodegradation of n-alkanes was much faster than polycyclic aromatic compounds(PAC).